Three's a Crowd—A Unique Combination of Coronary Artery Atresia, Fistula, and Stenosis: Multiple Congenital Coronary Artery Anomalies. Issue 4 (July 2020) - Pandya, Nischal R.; Venugopal, Prem; Wildschut, Jason; Alphonso, Nelson
The incidence of congenital coronary artery anomalies in the general population is low. The combination of various significant coronary artery anomalies in a single patient is not very common. We describe a case of a 20-month-old child with a unique combination of congenital coronary anomalies (atresia, stenosis, fistula) which were accurately delineated by multimodal imaging and successfully managed surgically.